INFLUENCE OF PHOSPHORUS CONTENT OF SEEDS ON THE PLANT GROWTH OF 11 VARIETIES OF DURUM WHEAT (TRITICUM DURUM DESF.) - Mazouz , Lakhdar; LEBBAL, Salim (Journal of Agricultural Sciences (Belgrade), 2026)
The phosphorus has an important role in the plant growth. Furthermore, the use of alternative methods, such as the cultivation of appropriate cultivars to satisfy the plant nutrient requirements and to reduce the negative effect of chemical fertilisers, is highly recommended. Thus, the aim of the present study was to screen the influence of the seed phosphorus content on the plant growth of 11 durum wheat (Triticum durum Desf.) varieties from numerous origins. Different morphological traits and their relation with the phosphorus quantities were investigated. These traits include root and aerial length, number of leaves, number of herbaceous tillers and number of ears. The obtained results revealed significant differences in the studied morphological characters among the examined wheat varieties. In addition, a positive correlation was recorded between the phosphorus levels in seeds and some morphological characters, particularly the aerial length, the number of leaves and tillers and the root length. It is concluded that higher phosphorus content in seeds has helped some varieties to achieve a good start. This suggests the necessity to consider this property when choosing durum wheat varieties for regions where P is scarce at sowing. It also fits into a broader global vision of sustainability by lowering the need for phosphate fertilisers.